The Analysis Performance of Project Delays in Pile Foundation Work - Steven Shui; Andri Irfan Rifai; Mulia Pamadi (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: Delays are common in construction projects. The term "project delay" refers to a project's completion date later than anticipated. Lack of performance by contractors or project managers in resolving issues can result in project delays. The factors that cause project delays must be considered to reduce delays. This study aims to examine the elements contributing to Batam island’s pile foundation construction delays. Findings: The factor of delays is an important key of the analysis to prevent delays in future projects Design/methodology/approach: This research uses a case study at Batam Island. The analysis is done with SPSS 26 program. Research limitations/implications: Analysis of delay caused by pile foundation in Batam island. Practical implications: Analysis of the delay caused by a project according to the result of the questionnaire. Originality/value: Original Paper Paper type: A Case Study